The 1915 Riots Sinhalese Memorial to Bonar Law - Peiris, James; Committee appointed at the Public Meeting of the Sinhalese (1915)
This document has been addressed to the right honourable Andrew Bonar Law, the majesty's principal secretary of state for the colonies, London by the humble memorial of the undersigned members of a committee appointed at a public meeting of the Sinhalese held in Colombo, the 25th day of September 1915.
Keywords: Race riots -- Sri Lanka; Politics and government -- Sri Lanka